Triazine Herbicide and NPK Fertilizer Exposure: Accumulation of Heavy Metals and Rare Earth Elements, Effects on Cuticle Melanization, and Immunocompetence in the Model Species Tenebrio molitor - Attilio Naccarato; Maria Luigia Vommaro; Domenico Amico; Francesca Sprovieri; Nicola Pirrone; Antonio Tagarelli; Anita Giglio (Toxics, 2023)
The increasing use of agrochemicals, including fertilizers and herbicides, has led to worrying metal contamination of soils and waters and raises serious questions about the effects of their transfer to different levels of the trophic web. Accumulation and biomagnification of essential (K, Na, Mg, Zn, Ca), nonessential (Sr, Hg, Rb, Ba, Se, Cd, Cr, Pb, As), and rare earth elements (REEs) were investigated in newly emerged adults of Tenebrio molitor exposed to field-admitted concentrations of a metribuzin-based herbicide and an NPK blend fertilizer. Chemical analyses were performed using inductively coupled plasma tandem mass spectrometry (ICP-MS/MS) supported by unsupervised pattern recognition techniques. Physiological parameters such as cuticle melanization, cellular (circulating hemocytes), and humoral (phenoloxidase enzyme activity) immune responses and mass loss were tested as exposure markers in both sexes. The results showed that NPK fertilizer application is the main cause of REE accumulation in beetles over time, besides toxic elements (Sr, Hg, Cr, Rb, Ba, Ni, Al, V, U) also present in the herbicide-treated beetles. The biomagnification of Cu and Zn suggested a high potential for food web transfer in agroecosystems. Gender differences in element concentrations suggested that males and females differ in element uptake and excretion. Differences in phenotypic traits show that exposure affects metabolic pathways involving sequestration and detoxification during the transition phase from immature-to-mature beetles, triggering a redistribution of resources between sexual maturation and immune responses. Our findings highlight the importance of setting limits for metals and REEs in herbicides and fertilizers to avoid adverse effects on species that provide ecosystem services and contribute to soil health in agroecosystems.